Flexible, binder-free and high-loading graphite paper cathodes for ultra-high capacity and long-life Al-graphite dual-ion batteries. (1st June 2021) - Zheng, Xiao; Zhao, Fangfang; Ma, Lei; Tang, Ruixian; Dong, Yanru; Kong, Guolong; Zhang, Yu; Niu, Sulin; Tang, Gen; Wang, Yue; Pang, Aimin; Li, Wei; et al.
Abstract: Aluminum batteries have received extensive research because of the safety, abundance and high capacity of Al anode. Most previous works are concentrated on improving the specific capacity of the cathodes, while other important issues such as cheap cathode-electrolyte system and high areal active material loading have often been overlooked. This paper reports that cheap graphite paper (GP) coupled with low price AlCl3 /Et3 NHCl ionic liquid (IL) electrolyte can form a practical Al dual-ion battery (ADIB). By adjusting the AlCl3 content in IL, the energy storage of GP with high-loading is improved. The ADIB exhibits 71 mAh g −1 at 200 mA g −1 with a loading of 15.16 mg cm −2, which is almost unattenuated over 1400 cycles. The GP cathode presents 47 mAh g −1 at 150 mA g −1 when the loading increased to 30.21 mg cm −2 . Even at an ultrahigh loading of 46.35 mg cm −2, the cathode can still achieve 75 mAh g −1 (3.5 mAh cm −2 ) at 40 mA g −1 for over 500 stable cycles. The high capacity is contributed by a self-activating process of AlCl4 − intercalation, which is closer to the diffusion-controlled battery behavior. The GPs simultaneously exhibit high areal capacity, energy/power density and long-life cycling performance which demonstrates their wide commercial prospects.